PROPOSED MODEL FOR GRAIN ALIGNMENT IN YBa2Cu3O7-x SUPERCONDUCTORS PREPARED BY MELT PROCESSING - Aristianto M.M.B. (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2009)
PROPOSED MODEL FOR GRAIN ALIGNMENTIN YBa2Cu3O7-x (123) SUPERCONDUCTORS PREPAREDBYMELTPROCESSING. Amodel for grain alignment in YBa2Cu3O7-x is proposed. The proposed model is based on experimental results that the grain alignment in coarse samples with average grain diameter of 57 μm is higher than that of fine samples with average grain diameter of 1.6 μm which were prepared bymelt processing. Other evidence, supported the proposed model, is the difference inmicrostructure of both samples, i.e. the grain in the fine samples tend to form domain-like structure, while in the coarse sample some large grain randomly oriented in the bulk and some grain aligned on the surface. The alignment of grain in coarse sample is due to capillary mechanism while in the fine samples the alignment could be due to capillary mechanism or sympathetic nucleation.